Reimbursement of sensor nodes and path optimization. (2021) - Bhuvaneshwari, C.; Manjunathan, A.
Abstract: In wireless sensor networks (WSNs) large numbers of sensor nodes are employed for various purposes. These sensors are placed in extreme condition where frequent monitoring of sensor health can't be made. Hence there is a need for monitoring the integrity of sensor data and fault detection. The data delivered after the deadline is also useless. The proposed method brings about the need for checking the path delay for all nodes in the WSN. The faulty node is identified based on modified adhoc on demand distance vector routing protocol (mAODV). After spotting the faulty node it may be replaced with actor node to provide data within deadline. Delay time (DTA) algorithm is used to calculate path delay between source and destination. The fault recovery algorithm (FRA) is used to replace the faulty node with actor node.